Galectin-related protein, a key contributor, drives diabetes-associated neuropathic pain - Danyang Chen; Jing Wang; Xiang-Jie Song; Zi-Jiao Ding; Qianqian Lou; Yuan-Yuan Chen; Meng-Yuan Wang; Xin-Lu Yang; Zhi Zhang; Juan Li; Wei Wang; Haitao Wang (Proceedings of the National Academy of Sciences, 2025)
Neuropathic pain associated with central sensitization is common in diabetic patients, but the underlying mechanisms remain unclear. Here, a proteomics screen identified a previously uncharacterized protein, galectin-related protein (LGALSL), which was significantly upregulated in cerebrospinal fluid and extracellular fluid of the anterior cingulate cortex (ACC) in diabetes-related neuropathic pain (DNP) model rats. Exogenous LGALSL administration reduced mechanical nociceptive thresholds by activating glutamatergic neurons in the ACC (ACC Glu ). Chemogenetic manipulations and functional assays revealed that neuron-derived LGALSL directly binds to vimentin on ACC astrocytes, activating those astrocytes. These activated astrocytes subsequently maintain ACC Glu hypersensitivity, driving mechanical hypersensitivity in diabetic rats. Blocking LGALSL–vimentin interactions with a synthetic peptide alleviated LGALSL-induced mechanical hypersensitivity. This study establishes LGALSL-dependent astrocyte-mediated hyperactivation of ACC Glu neurons as a new pathological mechanism of neuropathic pain in diabetes.